Chemical Composition, Phytochemical Screening and Antioxidant Activity of Acmella uliginosa (Sw.) Cass Leaves - Askal Maimulyanti; Anton Restu Prihadi; Iwan Safrudin (Indonesian Journal of Chemistry, 2016)
Acmella uliginosa (Sw.) Cass is widely used in traditional medicine and used in the treatment of many diseases. Extraction of component in leaves of Acmella uliginosa used methanol, ethyl acetate and n-hexane solvent. The percentage yield of extract from the leaves in methanol, ethyl acetate and n-hexane were 6.50, 0.49, and 0.66, respectively. Analysis of component in various extracts of Acmella uliginosa (Sw.) Cass leaves used Gas Chromatography-Mass Spectrometry (GC-MS). The various classes of phytochemicals were identified from fractions of methanolic leaves extract by GC-MS. Qualitative analysis of phytochemical constituents in methanol, ethyl acetate and n-hexane extract were tannins, flavonoids, saponin, alkaloid and steroid. Antioxidant activity of Acmella uliginosa leaves from Indonesia was carried out by using 1,1,diphenyl-2-picryl-hydrazine (DPPH) free radical scavenging assay. The IC50 of three extract was calculated. A comparative study determined that Acmella uliginosa in ethyl acetate extract showed the highest antioxidant potential (IC50 = 28.09 µg/mL) compared to methanol extract (IC50 = 44.31 µg/mL) and n-hexane extract (181.23 µg/mL) against DPPH free radicals.